Polyvinyl Alcohol Carbazate as a Polymer-Based Antitumoral Agent - Sellberg, Felix; Fröbom, Robin; Binder, Christian; Berglund, Erik; Berglund, David (Frontiers in Oncology, 2021)
Development of treatment resistance is a major concern during treatment of cancer, and there is an unmet need for therapeutic strategies with novel modes of action. Polyvinyl alcohol carbazate (PVAC) is a polymer compound with unique biological properties. Herein, we describe the antitumoral effects of PVAC. Three well-established cell lines GIST-T1, B16.F10, and A375 were used to determine the in vitro antitumoral effects of PVAC. Assessments included light microscopy, cell viability, cell cycle and apoptosis assays. In vivo treatment safety and efficacy were characterized in one immunocompetent (B16.F10) mouse model and one athymic nude (MDA-MB-231) mouse model. Excised tumors were measured, weighed, stained for Ki-67, CD3, and histopathologically evaluated. Intact PVAC expressed a nonlinear dose-response antitumoral effect in vitro, whereas its separate components, PVA and carbazate, did not display antitumoral effects alone. In vivo, PVAC induced a significant intratumoral CD3+ T-cell recruitment in immunocompetent mice (B16.F10), which was associated with tumor growth inhibition. Although growth inhibition was not significant in athymic mice (MDA-MB-231), histopathological evaluation detected an increase in stromal tissue and leukocyte infiltration. In conclusion, we present evidence for PVAC antitumoral effects both in vitro and in vivo. The mode of action was not elucidated in vitro, but a potential mechanism of in vivo activity was observed, characterized by an increase of immune cells into both immunocompetent and athymic mice. This finding warrants further study to validate its possible role as an immunomodulatory polymeric agent.